1971
DOI: 10.1507/endocrj1954.18.169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ACTH on Turnover of Phospholipids in Rat Adrenal Glands

Abstract: Time-course studies of 3H-choline incorporation into adrenal phospholipids revealed that the specific radioactivity reached to a maximum level at 9 hr after the isotope injection in untreated control animals, while in ACTH-treated animals, a maximum incorporation was already attained by 2 hr postinjection. The effect of ACTH on the incorporation was relatively prompt, the effect became evident as early as 1.5 hr after the treatment of animals. The rate of the incorporation in ACTH-treated animals was about twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

1972
1972
1986
1986

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Ichii et al(149) described that ACTH stimulated the incorporation of choline into phospholipid by adrenocortical postmitochondrial fractions. Ichii et al(149) described that ACTH stimulated the incorporation of choline into phospholipid by adrenocortical postmitochondrial fractions.…”
mentioning
confidence: 99%
“…Ichii et al(149) described that ACTH stimulated the incorporation of choline into phospholipid by adrenocortical postmitochondrial fractions. Ichii et al(149) described that ACTH stimulated the incorporation of choline into phospholipid by adrenocortical postmitochondrial fractions.…”
mentioning
confidence: 99%
“…The increased rate of 3H-choline incorporation into phospholipids of mitochondria as well as into microsomes was observed shortly after ACTH administration (Ichii, 1970, Ichii et al, 1971) and this might be attributable, at least in part, to the effect of ACTH on the rate of phospholipid exchange in mitochondria) membrane system in addition to on the biosynthetic system in microsomes. The i esponse of adrenal phospholipid to ACTH seems to be quite prompt and reached almost maximum level within a day after start of the treatment (Ichii et al, 1972), therefore, the low rate of phospholipid exchange observed in ACTH 3 days-mitochondria might possibly be explained by that the elevated rate of exchange has already taken place at early phase of ACTH-treatment. Increased phospholipid content in adrenal mitochondria) membranes 3 days after start of ACTH-treatment was detected (Ichii et al, 1972) and this might support the view mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…somes. A part of results of the preliminary experiment in which labeled liver microsomes were used as the donor of phospholipid has already been reported (Ichii et al, 1971). Blob et al(1971) presented evidences for the phospholipid exchange between inner and outer membranes of rat liver mitochondria in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations